Development of calcium-based heterogeneous catalyst for deoxygenation of triglycerides into green fuel / Nurul Asikin Mijan - Nurul Asikin , Mijan (2018)
The utilization of green fuel derived from biomass in industries and transportation has improved energy security by reducing the dependency on the non-renewable fossil petroleum. Deoxygenation process is one of the alternative pathways to produce green fuel via decarboxylation/decarbonylation (deCOx) reaction. Bonded oxygen molecules in the feedstock were removed in the form of CO2/CO gas in deCOx reaction. Acid catalyst is generally used for promoting deoxygenation reaction, however, the high acidity of the catalyst will promote coke formation at the end of the reaction. As a result, researchers have moved forward with the utilization of basic catalysts in deoxygenation reaction. Since, the study on implementation of basic catalyst in defying coke formation during the deoxygenation reaction still maintain unknown or limited. Hence, chapter 3 was focused on the development of high basic catalysts via surfactant assisted sonochemical method and the catalyst further explored in deoxygenation process. Due to the low deoxygenation activity shown by pure basic catalyst, the prospects of utilizing acid-base catalysts over transition metals (Ni, Zn, Fe, Co and W) supported CaO catalysts were further investigated and reported in chapter 4 and 5 with Co and Ni metals promoted catalyst found to be the most effective in catalyzing the deoxygenation reaction. Furthermore, the degree of coke formation also was found to be minimal at < 8.2 wt.%. With the effort to overcome low activity by TMO-CaO catalyst due low surface area and low desired acidic sites, extensive studies were focused on the utilization of mesoporous acidic support (SiO2-Al2O3) promoted NiO-CaO and Co3O4-CaO in chapter 6 to 8. The impact of Ca, Ni and Co metals oxides on the deoxygenation routes via deCOx was investigated. Ni-promoted catalyst exhibited highest deoxygenation activity and remarkable enhancement of deCOx reaction which is achieved due to the large existence of mildly acidic sites than strong acid and basic sites. Instead of using basic metal promoter, the use of neutral support (carbon-based support) was found to be effective in suppressing the coke formation (chapter 9). The coke was found to be < 4.2 wt.% after 4 consecutive deoxygenation runs. Overall studies, it can be concluded that the implementation of basic metal promoter and carbon-based catalyst in deoxygenation process will inhibit the growth of coke and would enhance catalyst stability.